Isoprene improves photochemical efficiency and enhances heat dissipation in plants at physiological temperatures - Pollastri, Susanna (Oxford University Press, 2014)
Isoprene-emitting plants are better protected against thermal and oxidative stresses. Isoprene may strengthen membranes avoiding their denaturation and may quench reactive oxygen and nitrogen species, achieving a similar protective effect. The physiological role of isoprene in unstressed plants, up to now, is not understood. It is shown here, by monitoring the non-photochemical quenching (NPQ) of chlorophyll fluorescence of leaves with chemically or genetically altered isoprene biosynthesis, that chloroplasts of isoprene-emitting leaves dissipate less energy as heat than chloroplasts of non-emitting leaves, when exposed to physiologically high temperatures (28–37 °C) that do not impair the photosynthetic apparatus. The effect was especially remarkable at foliar temperatures between 30 °C and 35 °C, at which isoprene emission is maximized and NPQ is quenched by about 20%. Isoprene may also allow better stability of photosynthetic membranes and a more efficient electron transfer through PSII at physiological temperatures, explaining most of the NPQ reduction and the slightly higher photochemical quenching that was also observed in isoprene-emitting leaves. The possibility that isoprene emission helps in removing thermal energy at the thylakoid level is also put forward, although such an effect was calculated to be minimal. These experiments expand current evidence that isoprene is an important trait against thermal and oxidative stresses and also explains why plants invest resources in isoprene under unstressed conditions. By improving PSII efficiency and reducing the need for heat dissipation in photosynthetic membranes, isoprene emitters are best fitted to physiologically high temperatures and will have an evolutionary advantage when adapting to a warming climate.